Determining Public Value of Infrastructure Projects: Case Studies in Yogyakarta Province, Indonesia - Laeli Nur Khanifah; Achmad Nurmandi (Magister Administrasi Publik, 2019)
Public infrastructure is very important for tourism and cultural activities in Yogyakarta as one of the largest tourist cities in Indonesia. The purpose of this study is to determine the public value of three public investment projects in Yogyakarta, including, Flyover, Jalan 0 Km, and Grahatama Library. Flyover represents infrastructure projects in the form of roads, zero KM represents one of Yogyakarta's biggest tourist destination icons, and Grahatama Library represents a difficult development project. This study uses the cost-effectiveness analysis of each project using qualitative methods through interviews and secondary data analysis of three research sites. This method is used to be able to analyze the publicity value of various types of infrastructure projects in Yogyakarta and how their implications are for the economy. The results show that the construction of the three projects has the potential to produce results that will improve community welfare and increase income distribution, implying that the project values investment costs. Thus, despite the fact that in connection with the cost of the Grahatama library project, far exceeds the short economic value it generates, in the long run, the existence of libraries by increasing public access to knowledge will contribute to regional development.